Genotoxicity Assays Published since 2016 Shed New Light on the Oncogenic Potential of Glyphosate-Based Herbicides - Charles Benbrook; Robin Mesnage; William Sawyer (Agrochemicals, 2023)
Controversy over the oncogenicity of glyphosate-based herbicides (GBHs) persists seven years after a 2015 IARC Monograph classified glyphosate/GBHs as “probably carcinogenic” to humans. Most regulatory authorities have concluded that technical glyphosate poses little or no oncogenic risk via dietary exposure. The US EPA classified glyphosate as “not likely” to pose cancer risk in 1991, a decision reaffirmed in reports issued in 2017 and 2020. A Federal Circuit Court of Appeals in the US vacated EPA’s assessment of glyphosate human-health risks in 2022 and required EPA to revisit old and take into account new data in its forthcoming, possibly final glyphosate/GBH reregistration decision. Divergent assessments of GBH genotoxicity are the primary reason for differing conclusions regarding GBH oncogenic potential. We assessed whether assays published since completion of the EPA and IARC reviews shed new light on glyphosate/GBH genotoxicity. We found 94 such assays, 33 testing technical glyphosate (73% positive) and 61 on GBHs (95% positive). Seven of 7 in vivo human studies report positive results. In light of genotoxicity results published since 2015, the conclusion that GBHs pose no risk of cancer via a genotoxic mechanism is untenable.